The Influence of Problem Based Learning (PBL) Model on Students Learning Outcome - Susilawati Susilawati; Aris Doyan (Postgraduate, University of Mataram, 2023)
This study aims to determine the effect of problem based learning models assisted by PhET simulations on student learning outcomes in wave material. This research is a type of quasi-experimental research with nonequivalent control group design. The population in this study were all students of class XI MAN 1 Mataram. The research samples were students in class XI MIPA 3 with a total of 31 people as the control class and students in class XI MIPA 4 with a total of 29 students as the experimental class. The test instrument used is in the form of multiple choice questions. The results of the analysis show that the average score of physics learning outcomes in the psychomotor domain in the experimental class is 3.43, while for the control class the average value is 3.06. Analysis of physics learning outcomes in the affective domain of the experimental class was 3.34, while for the control class the average value was 3.13. The results of the questionnaire analysis of student responses in the experimental class obtained an average of 63.63. The results of testing the hypothesis using the t-test obtained a tcount of 6.45 and a ttable of 2.00. Thus the value of tcount is greater than ttable then Ha is accepted and H0 is rejected. This means that there is an influence of the problem-based learning model assisted by PhET simulations on student learning outcomes in wave material.